SISTEM INFORMASI INVENTORY PADA CV. SAMUDRA LAUTAN BERKAT PASURUAN MENGGUNAKAN METODE SCRUM - Mochamad Ramadhani; Lambang Probo Sumirat; Slamet Kacung (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
This study aims to design a web-based inventory information system at CV. Samudra Lautan Berkat Pasuruan to improve the efficiency and accuracy of stock management. The previous manual process using Microsoft Excel was considered ineffective and prone to errors. The system was developed using the Agile Scrum methodology which allows for structured and flexible development. This study uses a descriptive approach with data collection through observation, interviews, and literature studies. The system is built using PHP and MySQL, and applies the FIFO method for stock management. The features developed include recording incoming and outgoing goods, reports, and stock monitoring by admins, warehouses, and leaders. The implementation results show that this system accelerates the recording and reporting process, minimizes human error, and supports more accurate decision making in inventory management.